2008
DOI: 10.1002/ibd.20380
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of inflammatory bowel disease in a German twin cohort: Results of a nationwide study

Abstract: This study confirms a stronger genetic influence in CD than in UC. The high preponderance in being affected of the first-born twin and the fact that concordance was only 35% for CD and 16% for UC monozygotic twins highlight the important role of environmental trigger factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
74
0
6

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 147 publications
(85 citation statements)
references
References 51 publications
1
74
0
6
Order By: Relevance
“…The primacy of environmental risk factors in the development of IBD is demonstrated in twin studies. The concordance rate for ulcerative colitis (UC) is less than 20 % and is around 50 % for Crohn's disease (CD) in monozygotic twins [2][3][4]. Of note, twin studies have not provided much support for a host genetic influence on the gut microbiota [5].…”
Section: The Gut Microbiota: the Proximate Environmental Risk Factor mentioning
confidence: 99%
“…The primacy of environmental risk factors in the development of IBD is demonstrated in twin studies. The concordance rate for ulcerative colitis (UC) is less than 20 % and is around 50 % for Crohn's disease (CD) in monozygotic twins [2][3][4]. Of note, twin studies have not provided much support for a host genetic influence on the gut microbiota [5].…”
Section: The Gut Microbiota: the Proximate Environmental Risk Factor mentioning
confidence: 99%
“…Except for highly penetrant Mendelian disorders, MZ twins exhibit a broad range (25%-95%) of disease discordance for most complex diseases that cannot be explained by classical genetics (Nance 1977). A recent report showed a discordance rate of 84% in MZ twins for UC (Spehlmann et al 2008). While, historically, twin-based studies have been employed for the identification of disease genes, recent interest in MZ twin studies has moved to mapping epigenetic changes in identical genomes that have precipitated into different phenotypes (Fraga et al 2005;Kaminsky et al 2009;Javierre et al 2010;Rakyan et al 2011a).…”
mentioning
confidence: 99%
“…A study done in German 9 showed that 35% of monozygotic pairs, but only 3% of dizygotic pairs, were concordant for the disorder. In 70% of discordant monozygotic pairs the first-born had IBD.…”
Section: Geneticsmentioning
confidence: 99%
“…In 70% of discordant monozygotic pairs the first-born had IBD. 9 Substantial phenotypic (location, behaviour, and age at diagnosis) concordance exists, both at diagnosis and longitudinally, in monozygotic twins. 10 Familial aggregation is confirmed.…”
Section: Geneticsmentioning
confidence: 99%